As German as Kafka Identity and Singularity in German Literature around 1900 and 2000 - Rock, Lene (Leuven University Press, 2019)
Since the turn of the 21st century, countless literary endeavors by 'new Germans' have entered the spotlight of academic research. Yet 'minority writing', with its distinctive renegotiation of traditional concepts of cultural identity, is far from a recent phenomenon in German literature. A hundred years previously, the intense involvement of German-Jewish intellectuals in cultural and political discourses on Jewish identity put a clear stamp on German modernism. This book is the first to unfold literary parallels between these two riveting periods in German cultural history. Drawing on the philosophical oeuvre of Jean-Luc Nancy, a comparative reading of texts by, amongst others, Beer-Hofmann, Kermani, Özdamar, Roth, Schnitzler, and Zaimoglu examines a variety of literary approaches to the thorny issue of cultural identity, while developing an overarching perspective on the 'politics of literature'.